The Impact of Library Services and School Facilities on Students’ Learning Process - Heri Wardana (Jurnal Pendidikan Rafflesia, 2026)
Students’ learning activities at school and their ability to keep up with the latest technological developments are greatly supported by the presence of a library. This facility serves as a vital resource that provides access to information to foster a culture of literacy. Through strong literacy skills, students can more easily understand academic subjects, develop their potential, and hone their creativity. The purpose of this study is to analyze the influence of the school library on the learning process of students at SMAN 16 Bekasi. This study employs an associative quantitative method involving a series of instrument tests and classical assumptions. The study population consists of 140 students at SMAN 16 Bekasi. A sample of 58 students was selected using random sampling. Data was collected by distributing an online questionnaire via Google Forms. The data analysis techniques used were classical assumptions, multiple linear regression, and hypothesis testing using SPSS 22 software. The findings of this study indicate that school libraries have a positive and significant impact on the learning process of students. The use of library services helps students identify their information needs, search for and locate relevant sources, and utilize them according to their needs. In addition, libraries help facilitate a shift in teaching methods from traditional approaches toward more modern ones, thereby enhancing the effectiveness and efficiency of the students’ learning process.